The Role of Job Satisfaction as a Mediator on the Implementation of Human Resource Information System (HRIS) On Employee Performance at PT. Hardo Soloplast - Sari, Ella Ayu Puspita; Waskito, Jati (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study investigates the influence of Human Resource Information Systems (HRIS) on employee performance with job satisfaction as a mediating variable at PT. Hardo Soloplast, within the broader context of digital transformation in HR management. Utilizing a quantitative approach and Partial Least Squares-Structural Equation Modeling (PLS-SEM) via SmartPLS 4, the research collected data from 64 randomly selected employees. Results indicate that HRIS significantly enhances both job satisfaction and employee performance, with job satisfaction partially mediating this relationship. While the study confirms the positive impact of HRIS, it treats HRIS as a singular construct without detailing how specific functionalities such as self-service portals, performance tracking, or automated workflows affect satisfaction and performance outcomes. Moreover, the reliance on simple random sampling within a single company limits the generalizability of findings, suggesting that future research should include multi-company comparisons or more diverse sampling strategies. The literature review could be enriched by addressing conflicting evidence and exploring conditions under which HRIS might yield negative effects, such as user resistance or inadequate training. This would provide a more comprehensive and critical understanding of HRIS implementation and its varied outcomes across organizational contexts.